2011
DOI: 10.1542/peds.2010-3022
|View full text |Cite
|
Sign up to set email alerts
|

Familial Aggregation of Autoimmune Disease in Juvenile Dermatomyositis

Abstract: We find strong familial aggregation of specific autoimmune diseases in families of children with juvenile dermatomyositis, suggesting that these conditions share pathogenic factors. Higher serum interferon-α in juvenile dermatomyositis patients with a family history of systemic lupus erythematosus suggesting that interferon-α is one such shared factor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
49
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 60 publications
(53 citation statements)
references
References 54 publications
4
49
0
Order By: Relevance
“…Another direction will be to investigate familial autoimmunity in broader terms, rather than focusing on the patterns of single diseases within families. Various combinations of autoimmune diseases have been shown to cluster within families and individuals,1 51 52 and shared heritable pathogenic factors, such as dysregulation of the interferon-α system in several autoimmune conditions, have been suggested 53 54. While autoimmune diseases may have genetic and environmental risk factors in common, the interplay of such factors may influence the particular autoimmune phenotypes that are expressed 55 56…”
Section: Discussionmentioning
confidence: 99%
“…Another direction will be to investigate familial autoimmunity in broader terms, rather than focusing on the patterns of single diseases within families. Various combinations of autoimmune diseases have been shown to cluster within families and individuals,1 51 52 and shared heritable pathogenic factors, such as dysregulation of the interferon-α system in several autoimmune conditions, have been suggested 53 54. While autoimmune diseases may have genetic and environmental risk factors in common, the interplay of such factors may influence the particular autoimmune phenotypes that are expressed 55 56…”
Section: Discussionmentioning
confidence: 99%
“…Myositis patients and their close relatives are more likely to develop other autoimmune diseases, suggesting shared genetic architectures 4,5 . Moreover, early candidate-gene, case-control studies of the IIM in Caucasians demonstrated strong, reproducible associations with the HLA 8.1 ancestral haplotype (AH8.1) and the DRB1 03:01 allele in particular, although, with the exception of sporadic inclusion body myositis in which recombinant mapping suggests a susceptibility region spanning 172 kb and encompassing HLA-DRB3, HLA-DRA and BTNL2 6 , the independent impact of alleles comprising AH8.1 has not been determined 7,8 .…”
Section: Introductionmentioning
confidence: 99%
“…Niewold et al found that functional type I IFN activity was increased in serum from juvenile dermatomyositis (JDM) patients [18], and similar findings have been observed in adult DM patients by Dastmalchi et al [19]. Not all patients exhibit high levels of circulating type I IFN, and this may represent a form of molecular heterogeneity in DM, as current evidence would suggest that the type I IFN pathway activation is influenced by heredity to some degree [20,21]. Also, in JDM patients, it has been shown that high serum type I IFN is correlated with autoantibodies against RNA-binding proteins, explaining some of the heterogeneity between patients in circulating type I IFN [22•].…”
Section: Type I Ifnsmentioning
confidence: 72%